The attributes of customers behavior to use of Ar- Rahnu in Kota Bharu, Kelantan - Mohamad Firdaus Ibrahim; Siti Nur Farah Shaharuddin; Siti Nurhajarriah Md Tahir; Siti Rahimah Muhamad Don (2022)
To conclude, chapter two elaborates in detail by using past research to construct each variable. This chapter also contains the reviews of the Attributes of customers' behavior to use Ar- Rahnu in Kota Bahru, Kelantan. Besides, chapter two also proposed a conceptual model which is constructed to look over the connection between the independent variable (Sharia view, Pricing system, Customer service, and Locality) and dependent variable (The attributes of customer to use Ar-Rahnu). Consequently, hypotheses were prepared based on each variable in this study. Chapter three is going to analyze the research methodology in studying the initiated hypotheses.